Superconducting properties of Ce-substituted TaSr2(Gd,Ce) 2Cu2Oy - Abd-Shukor R.; Kek C.A.; Yeoh W.K. (2023)
A layered cuprate TaSr2 $$(\rm Gd)_(1+x)$$ $$(\rm Ce)_(1-x)$$ Cu 2 $$(\rm O)_y$$ for x = 0.4-0.8 has been successfully synthesized by solid state reaction. X-ray powder diffraction analysis indicates that nearly all the peaks from the samples can be indexed to a single phase of Ta-1222. The sample with nominal composition TaSr 2Gd1.6Ce0.4Cu2 $$(\rm O)_y$$ showed a tetragonal structure with lattice parameters a = 3.858, c = 28.81? with space group most likely I4/mmm. The TaSr2 $$(\rm Gd)_(1+x)$$ $$(\rm Ce)_(1-y)$$ Cu2 $$(\rm O)_y$$ compound exhibits a narrow superconducting region near x = 0.6 with T c-onset = 30 and T c-zero=10 K as determined by d.c. electrical resistance versus temperature measurements. 2006 Springer Science + Business Media, Inc.